The heterogeneous number in Baltic - Petit, Daniel (Baltistica, 2023)
The ‘heterogeneous number’ refers to dual or plural forms including two items one of which is not directly denoted by the sum. An example is Spanish padres ‘parents’ which includes [father] + [mother], but is expressed by the plural of padre ‘father’, leaving implicit the ‘mother’. The aim of this paper is to describe the extension of the heterogeneous number in the Indo-European languages and particularly in Lithuanian, where a distinction between tė́vai ‘fathers’ (homogeneous plural) and tėvaĩ ‘parents’ (heterogeneous plural) has often been associated with a shift of the accentual paradigm. It can be shown that the heterogeneous number is a recent development in Lithuanian and derives from a collective meaning (‘group of fathers’), whose accentual properties can be traced back to the Indo-European collective.
Keywords: Lithuanian; grammatical number; plural; dual; accentual paradigm